SYNERGIES IN EDUCATION: INTEGRATING CHARACTER, LITERACY, AND TECHNOLOGY FOR ENHANCED OUTCOMES: CURRENT PERSPECTIVES FROM GLOBAL EDUCATION EXPERTS - Dede Gustian; Marzuki; Nukman; Yulian Purnama; Dayan Abdurrahman (Adisam Publisher, 2024)
This literature review delves into the multifaceted transformation of education through the lens of character development, literacy promotion, and the strategic integration of technology. Drawing from the perspectives of global education experts, the study navigates the evolving landscape of education in Indonesia, highlighting challenges and opportunities within its decentralized system. The significance of character development is underscored, emphasizing its role in shaping well-rounded individuals capable of navigating a rapidly changing world. Exploring Literacy in the modern educational context, the review defines its broader scope, encompassing traditional and digital forms. Global initiatives to improve literacy rates and successful programs are examined, shedding light on effective strategies for fostering a reading culture and enhancing critical thinking skills. Technology integration is investigated as a transformative force, redefining teaching and learning experiences globally. The literature showcases initiatives and case studies that illustrate successful technology integration in education while addressing challenges and proposing solutions for maximizing benefits. The synthesis of these components reveals an intricate interplay between character development, Literacy, and technology. The interconnectedness of these elements forms the foundation for a holistic educational approach, preparing students both academically, ethically and technologically. Global perspectives on integrated approaches showcase exemplary educational systems, emphasizing the transformative potential of a comprehensive, student-centered education.